2002
DOI: 10.1086/342774
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Haplotype of the RET Proto-Oncogene Is a Risk-Modifying Allele in Hirschsprung Disease

Abstract: Hirschsprung disease (HSCR) is a common genetic disorder characterized by intestinal obstruction secondary to enteric aganglionosis. HSCR demonstrates a complex pattern of inheritance, with the RET proto-oncogene acting as a major gene and with several additional susceptibility loci related to the Ret-signaling pathway or to other developmental programs of neural crest cells. To test how the HSCR phenotype may be affected by the presence of genetic variants, we investigated the role of a single-nucleotide poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 16 publications
(13 reference statements)
7
34
1
Order By: Relevance
“…In the current series a variant allele of RET exon 14; S836S (c2508C > T) was detected that has been found in no other Asian series (Garcia-Barcelo et al 2003;Wu et al 2005;Sakai et al 2000) and was detected in reduced frequency compared with healthy subjects in Italian HSCR (Griseri et al 2000(Griseri et al , 2002. In our HSCR, the minor allele in this polymorphism was found exclusively in patients of Malay-Thai extraction who had LSD.…”
Section: Discussionsupporting
confidence: 53%
“…In the current series a variant allele of RET exon 14; S836S (c2508C > T) was detected that has been found in no other Asian series (Garcia-Barcelo et al 2003;Wu et al 2005;Sakai et al 2000) and was detected in reduced frequency compared with healthy subjects in Italian HSCR (Griseri et al 2000(Griseri et al , 2002. In our HSCR, the minor allele in this polymorphism was found exclusively in patients of Malay-Thai extraction who had LSD.…”
Section: Discussionsupporting
confidence: 53%
“…Several association and haplotype studies also support this hypothesis. 26,32,33 Conserved haplotypes could be constructed using the alleles identified for different markers in and around the RET gene. 24,34 -36 Carrasquilo et al 34 used the highest number of SNPs in and around the RET locus.…”
Section: Discussionmentioning
confidence: 99%
“…Two SNPs were located in intron 1 (IVS þ 6000A4C/rs2435362 and IVS1 -126G4T/rs2565206 (http://www.ncbi.nlm.nih.gov/SNP/) and the following SNPs were from exon 2 (c135G4A/A45A, rs1800858), 25 exon 7 (c1296G4A/rs1800860), 25 exon 14 (c2508C4T/ S836S, rs1800862) 25 and intron 19 (IVS19 þ 47C4T). 26 Of the four microsatellite markers, two were located upstream of RET, namely D10S1100 27 (300 kb upstream) and M353 28 (80 kb upstream), one located within intron 5, MRETint5, 28 and one is located 38 kb downstream the RET gene, s-TCL2 28 ( Figure 1).…”
Section: Genotypingmentioning
confidence: 99%
“…Functional analyses of M1064 failed to demonstrate significant changes in the activity of RET (31 ), and experiments in transgenic mice indicated that RET51 is not required for the development of the ENS (40 ). However, based on the demonstration of the formation of homoand heterodimers between RET9 and RET51, it has recently been suggested that there may be a critical role for the RET51:RET9 ratio in addition to that of the absolute amounts of the two isoforms (41 ).…”
Section: Sequence Alterations In Ret and Gdnfmentioning
confidence: 99%